2014
DOI: 10.1111/ijpp.12148
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation management by community pharmacists in New Zealand: an evaluation of a collaborative model in primary care

Abstract: Community-pharmacist-led anticoagulation care utilizing point-of-care testing and computerized decision support is safe and effective, resulting in significant improvements in TTR. Our results support wider adoption of this model of collaborative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…A mean TTR of at least 60% is needed for a patient to have effective oral anticoagulation . Two recent studies from community pharmacist‐based AMSs in New Zealand reported mean TTR around 75% . In our study, adherence to DOACs was also high (mean DOAC adherence at baseline: 86.4%; 73.9% of patients with DOAC adherence ≥ 80%), considering that a cut‐off of 80% is often used to distinguish between adherence and non‐adherence .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A mean TTR of at least 60% is needed for a patient to have effective oral anticoagulation . Two recent studies from community pharmacist‐based AMSs in New Zealand reported mean TTR around 75% . In our study, adherence to DOACs was also high (mean DOAC adherence at baseline: 86.4%; 73.9% of patients with DOAC adherence ≥ 80%), considering that a cut‐off of 80% is often used to distinguish between adherence and non‐adherence .…”
Section: Discussionmentioning
confidence: 88%
“…Limited information is available on the quality of oral anticoagulant management in community pharmacy‐based AMSs . Few studies in this setting have reported a mean TTR for patients on VKA (ranging from 67% to 84%) .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Anticoagulation management can be effectively carried out by a range of staff members; indeed there is strong evidence that community management utilising computer-assisted dose adjustment can improve when led by pharmacists rather than primary care general practitioners; TTR improving from 71.4% to 84.1% in one New Zealand based study in spite of no increase in point of care INR testing. 34 The 80% adherence to the algorithm by pharmacists compared to the 70% adherence by doctors was the most important factor influencing TTR rather than the specific details of the algorithm. Poorer control achieved by doctors compared to pharmacists (TTR 67.4% vs 75.1%) in another study was related to poorer adherence to computer dosing recommendations by doctors, with doctors over-riding the algorithm up to 50% of the time when INR was below range and tending to under-dose patients, mistakenly believing their own dose adjustments were better than the computer program which had been developed using large amounts of patient data.…”
Section: Discussionmentioning
confidence: 94%
“…As systems employing algorithm‐based dosing and promoting adherence to them could improve clinical outcomes on a global scale, feedback to centres to improve patient outcomes by practising in a more guideline concordant manner is recommended. Anticoagulation management can be effectively carried out by a range of staff members; indeed there is strong evidence that community management utilising computer‐assisted dose adjustment can improve when led by pharmacists rather than primary care general practitioners; TTR improving from 71.4% to 84.1% in one New Zealand based study in spite of no increase in point of care INR testing . The 80% adherence to the algorithm by pharmacists compared to the 70% adherence by doctors was the most important factor influencing TTR rather than the specific details of the algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies utilized more than one implementation strategy, with a mean of 6.5 implementation strategies (range, 1‐36 strategies) identified per article. For example, Harrison et al implicitly or explicitly described a total of eight implementation strategies to implement and determine the effectiveness of a community pharmacist disease state management service for anticoagulation . The article described use of one “evaluative and iterative strategy” to develop and implement tools for quality monitoring; two “train and educate stakeholders” strategies, which involved conducting educational meetings and distributing educational materials; two “support clinicians” strategies of revising professional roles and facilitating the relay of clinical data to providers; two “utilize financial strategies” by using other payment schemes and accessing new funding; and one “change infrastructure” strategy of changing elements of the physical structure and equipment.…”
Section: Resultsmentioning
confidence: 99%